Human serum folate can be measured using folate binding protein linked to enzyme-labeled protein ligand binding assay (ELPLBA) as well as ELISA - Muhamad Arif Budiman; Mohamad Sadikin; Ani Retno Prijanti (Indonesian Society for Biochemistry and Molecular Biology, 2018)
Background: Folate is an important substance used for purine and pyrimidine nucleotide synthesis. One measurement of folate that already establishes is using ELISA (Enzyme-linked immunosorbent assay) method. Folate binding protein is a protein that can bind folate, therefore it considered can be used as a tool that can replace antibody dependent ELISA method. Objectives: The aim of this research was to create a method for folate measurement in serum called Enzyme-labeled protein ligand binding assay (ELPLBA) by replacing antibody as used in ELISA method with folate binding protein (FBP) that purified from the whey of milk. Methods: The method is tested using 20 serum samples and compared to ELISA. Folate binding protein was purified from bovine’s milk using ammonium sulfate up to 90% saturated, DEAE-cellulose anion exchange chromatography and affinity chromatography. SDS-PAGE and western blot were used to establish the protein band of FBP that has molecular weight of 25-35 kDa. ELPLBA was arranged with stationary phase using aminohexyl-agarose, and folic acid linked on it using carbodiimide. Results: The result show there was no significant difference of folate concentration between ELPLBA (14.804 ± 2.795) and ELISA method (13.859 ± 3.638), p = 0.363. Conclusion: ELPLBA method show similarity for determination of folate in serum which was the same as standard folate measurement (ELISA).